Reversibility : politics under conditions of uncertainty - Behr, Hartmut (Montreal ; Chicago : McGill-Queen's University Press, 2024)
"Western modernity is characterized by instrumental relations between humans and nature, as well as between humans themselves, that have caused irreversible environmental and social exploitation and degradation. Many policy documents, such as those by the United Nations Environment Programme, warn of the uncertainty and unpredictability of our precarious conditions due to our social and ecological interrelations and interdependencies. Accepting that our position in the world does not allow us secure knowledge of the consequences of politics, Reversibility - Politics under Conditions of Uncertainty asks how we can act politically in a responsible way when we cannot predict the outcomes of our decisions. Hartmut Behr diagnoses Western modernity and its manifold crises as dominated by the view that fellow humans and natural environments are merely means to our individual ends. Behr introduces a novel ethics of self-restraint and the principle of reversibility - a commitment to political actions whose effects shall not be indefinite or immutable - to build a policy framework that demands both ethical and practical reflection on the conditions of action and that accounts for the limitations under which we act and live. Identifying an urgent need for re-thinking political progress and for policy reform, Reversibility - Politics under Conditions of Uncertainty presents a new understanding of the self and of political responsibility centred in a genuine acknowledgment of the human condition."--
Questioning Uncertainty and Contingency -- Ontological and Epistemological Implications -- Ethical Consequences -- Self-restraint: Reflections on a 'Self' -- From Ethics to Action -- The Triangulation of Perspectivity and Negation with Noesis -- Contingency and Non-linearity -- Grooving the Unknown, Three Conclusions, and Illustrations of Reversibility in Practice -- Normative-Interpretivist and Rationalist Policy Analysis: The Significance of Context -- Responding to the Anthropocene.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 17, 2024).
JSTOR
Keywords: Political science -- Philosophy; Political ethics; Contingency (Philosophy); Uncertainty; Morale politique; Contingence (Philosophie); Incertitude; PHILOSOPHY / Political